2016
DOI: 10.1111/1755-5922.12195
|View full text |Cite
|
Sign up to set email alerts
|

The randomized clinical trial of coenzyme Q10 for the prevention of periprocedural myocardial injury following elective percutaneous coronary intervention

Abstract: Introduction:Periprocedural myocardial injury (PMI) following elective percutaneous coronary intervention (PCI) is an important therapeutic concern with remaining some mortality and morbidity. To the best of our knowledge, there is no published study that investigates the potential benefit of CoQ10 in preventing PMI following elective PCI. Methods:In a randomized, clinical trial, 100 patients who scheduled for elective PCI were allocated in to the intervention (n=50) and control group (n=50). The intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In a randomized, clinical trial, the intervention group of 50 patients received a 300 mg loading dose COQ10 12 hours before the procedure. No significant change was reported in the level of cardiac biomarkers but there was a significant reduction in high sensitive C-reactive peptide level in COQ10 group [146]. This supports the evidence that COQ10 attenuates inflammatory reactions.…”
Section: Cardiac Surgery and Percutaneous Coronary Interventionsupporting
confidence: 67%
“…In a randomized, clinical trial, the intervention group of 50 patients received a 300 mg loading dose COQ10 12 hours before the procedure. No significant change was reported in the level of cardiac biomarkers but there was a significant reduction in high sensitive C-reactive peptide level in COQ10 group [146]. This supports the evidence that COQ10 attenuates inflammatory reactions.…”
Section: Cardiac Surgery and Percutaneous Coronary Interventionsupporting
confidence: 67%
“…The second trial among 100 patients showed that 300 mg coenzyme Q10 12 hours before elective PCI could not reduce PMI. However, it significantly decreased hs‐CRP …”
Section: Discussionmentioning
confidence: 92%
“…24 Recently in 2 randomized trials, we evaluated the effect of 1200 mg pentoxifylline and 300 mg coenzyme Q10 for the prevention of myocardial injury following elective PCI. 25,26 In the first trial, a loading dose of 1200 mg pentoxifylline before elective PCI in 85 patients could not lead to a significant result. 25 The second trial among 100 patients showed that 300 mg coenzyme Q10 12 hours before elective PCI could not reduce PMI.…”
Section: Comparison With Other Trialsmentioning
confidence: 99%
“…All showed a beneficial effect except one [ 74 ]. In this particular study, patients were pretreated with 300 mg CoQ10 only 12 h before the procedure and a reduction of the preprocedural myocardial injury following elective percutaneous coronary intervention was not observed, although the hs-C reactive protein significantly decreased [ 28 ]. This lack of effectiveness in the treatment with CoQ10 may be due to an insufficient increase in the plasma levels of CoQ10 since plasma ubiquinol concentration had nearly reached a steady state by 2 weeks after the beginning of the treatment [ 55 , 74 ].…”
Section: Coq10 In Cardiac Surgery and Coronary Arterial Disease (Cad)mentioning
confidence: 99%